2021
DOI: 10.3389/fonc.2021.644860
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Metastasis in Newly Diagnosed Esophageal Cancer: A Population-Based Study

Abstract: BackgroundThe hepatic metastasis pattern of esophageal cancer (EC) has not been fully explored. The primary objective of this study was to explore the predictors of esophageal cancer with hepatic metastasis (ECHM) at the time of diagnosis. In addition, we also analyzed the factors affecting ECHM prognosis.MethodsWe used the Surveillance, Epidemiology and End Result (SEER) database to identify ECHM patients at the time of initial diagnosis. The ECHM predictors were identified using multivariate logistic regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…This study identified five independent risk factors of ECBM: age <65 years, male sex, stage T1, advanced N stage, and non-bone organ metastases. Based on previous studies, the independent risk factors for liver metastasis of EC include age (younger), primary tumor site (middle and lower segments), degree of differentiation (poor), histology (adenocarcinoma), T stage (T1), N stage (advanced), and extrahepatic organ metastases ( 7 ). Meanwhile, the independent risk factors for lung metastasis of EC include the degree of differentiation (poor), histology (squamous cell carcinoma), T stage (T1 and T4), N stage (advanced), race (black), and non-lung organ metastases ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study identified five independent risk factors of ECBM: age <65 years, male sex, stage T1, advanced N stage, and non-bone organ metastases. Based on previous studies, the independent risk factors for liver metastasis of EC include age (younger), primary tumor site (middle and lower segments), degree of differentiation (poor), histology (adenocarcinoma), T stage (T1), N stage (advanced), and extrahepatic organ metastases ( 7 ). Meanwhile, the independent risk factors for lung metastasis of EC include the degree of differentiation (poor), histology (squamous cell carcinoma), T stage (T1 and T4), N stage (advanced), race (black), and non-lung organ metastases ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the results obtained from the two models are largely concordant, indicating that the statistical analyses are stable and reliable. According to recent reports, the following factors are associated with an increased risk of all-cause death in patients with liver metastasis: sex (male), age (advanced), histology (squamous cell carcinoma), other organ metastases, and therapy (no treatment) ( 7 ). In patients with lung metastasis, the following factors are associated with increased all-cause death: age (advanced), non-lung organ metastases, and therapy (no treatment) ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Poorly differentiated EC had a worse prognosis due to the higher rate of lymph node metastasis and distant organ metastasis rate (such as liver metastasis) ( 12 ). Further, the pathological grade could also guide adjuvant therapy after neoadjuvant therapy ( 12 , 13 ).…”
Section: Discussionmentioning
confidence: 99%